O nieprawidłowym stosowaniu narzędzi statystycznych w badaniach ankietowych - Halina Widła, Halina Widła (Neofilolog, 2019)
The article explores common mistakes made while interpreting statistics in questionnaire studies, which may reflect insufficient training in research methodology. It reveals problems in qualitative and quantitative analysis in the published literature. It also discusses the possible reasons why errors occur in the process of constructing diagrammatic representations of the collected data. Examples of errors as they occur in published articles are also cited to prove that such problems are far from being hypothetical and do appear in research reports. They are mainly reflective of erroneous beliefs concerning statistical significance testing, chi-square analysis, covariance statistical corrections, as well as presentation of statistically inaccurate results.